Design And Validity Of An E-Assessment Four Tier Multiple Choice To Assess Science Literacy Skills Of Students - Febriasri, Monika (Universitas Negeri Padang, 2025)
The low level of scientific literacy in parabolic motion material is a problem in physics education at the high school level. The low level of students' scientific literacy is caused by the lack of students' ability to understand physics concepts.Assessment instruments that specifically assess students' science literacy skills on the concept of parabolic motion are still limited. This study aims to develop a valid four tier multiple choice e-assessment to assess students' science literacy skills on parabolic motion material. This study is a research and development (R&D) using the Plomp model. The developed e-assessment was validated by three experts. The data collection instruments used were teacher evaluation sheets, self-evaluation sheets, and validation sheets. The results of the validity analysis showed that the e-assessment was in the valid category in terms of construction feasibility, material substance feasibility, visual communication feasibility, and language feasibility. From the validation results with an average value of 0.95, it shows that the four tier multiple choice e-assessment to assess students' science literacy skills is declared valid and feasible to use.